Delineation of the Feline Hippocampal Formation: A Comparison of Magnetic Resonance Images With Anatomic Slices - Gruber, Isabella; Kneissl, Sibylle; Probst, Alexander; Pakozdy, Akos (Frontiers in Veterinary Science, 2019)
The hippocampal formation (HF) is a relevant brain structure that is involved in several neurological and psychiatric diseases. In cats structural changes of the HF is associated with epilepsy. The knowledge of detailed anatomy of this brain region may lead to the accurate diagnosis and development of better therapy. Among the research findings are discrepancies, which may be due to different definitions being used, according to anatomical guidelines and boundaries, as well as different magnetic resonance (MR) protocols. The aim of this study was to evaluate the anatomical borders of the HF on transverse MR images and correlated anatomic sections in three cats. The boundaries of the HF were mostly visible in the formalin fixed anatomic sections, except in the areas where the hippocampus proper exchanges into the subicular complex. Also, the delineation of the anterioventral part and the latero-caudal borders of the HF are not clearly defined. Based on our preliminary results these problems are reinforced on MR images, and further histological and anatomical research must be done to find a way to delineate these neurologic structures accurately.